A CASE OF CHRONIC LIVER DISEASE. HEV INDUCED OR CRYPTOGENIC ? - Saeed, Farrukh; Iftikhar, Raheel; Saif, Mohsin (Journal of Ayub Medical College Abbottabad, 2006)
Hepatitis E virus (HEV) infection is known to cause epidemic outbreaks as well as sporadic disease in many parts of the world. Clinical presentation of hepatitis E varies from acute icteric viral hepatitis to severe disease with fulminant hepatic failure, and anicteric infection (no jaundice but with ALT elevation). According to available data HEV infection does not lead to chronic liver failure. We are reporting a case of 37 years old army soldier who was admitted as a case of HEV induced acute viral Hepatitis. Later he was found to have chronic liver disease (CLD) with persistence of HEV antibodies and absence of any other detectable cause of CLD. Keywords: HEV ,Persistent HEV Antibodies, Chronic Liver Disease